2004
DOI: 10.2174/1567202043480189
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous Facilitation: From Molecular Mechanisms to Persistent Pain

Abstract: It is well documented that sensory transmission, including pain, is subject to endogenous inhibitory modulatory influences at dorsal horn of the spinal cord. Recent results, from behavioral to molecular studies, demonstrate that endogenous modulatory systems are bi-phasic, including inhibitory as well as new facilitatory systems. In this review, we propose the existence of endogenous facilitatory systems in the brain, and review evidence supporting the hypothesis. We believe that understanding molecular and ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 43 publications
0
16
0
1
Order By: Relevance
“…GABA(c-aminobutyric acid)-and glycinergic spinal circuits play important role in the development of inflammatory pain (Robinson et al, 2004). It was suggested that spinal inhibition prevents a significant portion of deep dorsal horn neurons from becoming Fig.…”
Section: Discussionmentioning
confidence: 99%
“…GABA(c-aminobutyric acid)-and glycinergic spinal circuits play important role in the development of inflammatory pain (Robinson et al, 2004). It was suggested that spinal inhibition prevents a significant portion of deep dorsal horn neurons from becoming Fig.…”
Section: Discussionmentioning
confidence: 99%
“…However, compelling evidence demonstrates that descending control is bi‐directional via inhibitory and facilitatory systems. In addition to activating descending inhibitory pathways, peripheral nociceptive afferents are also capable of activating descending facilitatory pathways, particularly in pathological conditions (Robinson et al ., 2004). Sustained activation of descending facilitation increases excitability of spinal nociceptive neurons and in turn evokes neuroplasticity of some supraspinal structures including the ACC and RVM (Wei et al ., 1999; Porreca et al ., 2002; Robinson et al ., 2002), suggesting that sustained activation of descending facilitation could underlie some states of inflammatory and neuropathic pain (Porreca et al ., 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the specific cascade of changes that generate and maintain central sensitisation would significantly expand our ability to design targeted therapies to treat the central sensitisation that occurs following many types of skeletal pain. These neurochemical and electrophysiological changes appear to occur in the ascending and descending pain pathways of the spinal cord, brainstem, thalamus and cerebral cortex, and all of these changes may contribute to the amplified perception of skeletal pain (Basbaum & Fields, 1978;Gebhart, 2004;Robinson et al, 2004;Hunt, 2009;Latremoliere & Woolf, 2009;Woolf, 2011;Yoshida et al, 2013).…”
Section: Central Sensitisation and Skeletal Painmentioning
confidence: 99%